THE ANALYSIS OF GRAMMATICAL ERROR MADE BY THE STUDENTS IN WRITING RECOUNT TEXT (A CASE STUDY OF SMA NEGERI 1 PEUSANGAN) - INTAN AZUHRA; ISWADI; Misnar (Journal of English Education and Social Science, 2022)
The research of an analysis of grammatical error made by the students in writing recount text has beendone at SMAN 1 Peusangan. It was begun from October 2 2020 until October 3 2020. The problem ofthis research is; What are the most common types of grammatical errors made by the students in writingrecount text. Based on the research problem, there is one purpose of the research, namely; to find outthe most common types of grammatical errors made by students in writing recount text. The scope ofthis research focused on the grammatical errors made by 1st grade students of SMAN 1 Peusangan inwriting recount text. This research is designed as qualitative research using ‘test’ as the instrument ofthe research, the data is then analyzed with three steps of procedure, namely: data reduction, datadisplay, and data verification/conclusion drawing. The results of the research on the grammatical errorsmade by 1st grade students of SMAN 1 Peusangan in writing recount text showed that, capitalization wasthe most frequent error made by the 1st grade students of SMAN 1 Peusangan with the percentage of19%, meanwhile run-on sentence was the least frequent error made by the students with the percentageof 0%. Cause of error in intralingual error contributed up to 55% or 165 errors, followed by interferenceerror which contributed up to 35% or 107 errors, and the last is developmental error that contributed upto 10% or 30 errors. Based on the results of research, it was concluded that the 1st grade students of SMAN1 Peusangan often avoid the systematic of writing without capitalize several types of word like name ofplace, country, people and also the first letter of a new sentence. Conclusion was stated based on theresult that showed capitalization had the biggest contributions on students’ grammatical errors.Key Words: Grammatical Error, Recount Text